A highly stretchable strain sensor based on CNT/graphene/fullerene-SEBS. Issue 19 (18th March 2020) - Pan, Shirui; Pei, Zhen; Jing, Zhu; Song, Jianqiao; Zhang, Wendong; Zhang, Qiang; Sang, Shengbo
Abstract : Recently, highly stretchable strain sensors have attracted considerable attention. Identifying alternatives to sensitive unit materials and flexible substrates is critical in the fabrication of sensors. Abstract : Recently, highly stretchable strain sensors have attracted considerable attention. Identifying alternatives to sensitive unit materials and flexible substrates is critical in the fabrication of sensors. Herein, a trinary hybrid carbon material consisting of carbon nanotubes (CNTs), graphene, and fullerene was chosen due to its dense interconnections and robust mechanism. Additionally, the cost-effective fabrication of styrene ethylene butylene styrene (SEBS) provides a platform for the strong adhesion of substrates, which contributes to the strong interaction between the substrates and the sensitive unit materials. Furthermore, the intrinsically high elasticity of SEBS allows the sensors to endure large stretching ranges. Owing to the above-mentioned merits, the fabricated sensor based on CNT/graphene/fullerene-SEBS has a high conductivity of 5.179 S m −1, a moderate gauge factor (GF) of 15, an optimum stretching range of 203%, a linearity of 136% ( R 2 = 0.998), and adaptive-rate repeatability, which reveals its potential in the fields of human motion monitoring and scalable applications.